Initial validation of a short version of the PERMA profiler in a national sample of rural veterans - Umucu, Emre; Granger, Teresa Ann; Pan, Deyu; McGee, Traci; Han, Eunae; Yates, Jim; Barnas, John; Barter, Crystal; Lee, Beatrice (Frontiers in Public Health, 2024)
BackgroundMilitary veterans residing in rural areas face unique challenges that can impact their wellbeing, including limited access to healthcare resources, social isolation, and distinct environmental stressors. Despite growing interest in veteran wellbeing, there remains a gap in understanding how service-connected disabilities and health conditions intersect with wellbeing in rural contexts.MethodsThis study employed a comprehensive approach to investigate the relationships between wellbeing, service-connected disabilities, and health outcomes among rural veterans. First, a short version of the PERMA Profiler was psychometrically validated for use among rural veterans. Then, associations between wellbeing and mental/physical health outcomes were examined. Lastly, differences in wellbeing between veterans with and without service-connected disabilities were evaluated.ResultsThe psychometric validation of the short-form PERMA Profiler yielded robust results, establishing its reliability and validity for assessing wellbeing among rural veterans. Significant positive associations were found between wellbeing and mental/physical health outcomes. Moreover, rural veterans with service-connected disabilities exhibited lower wellbeing scores compared to those without such disabilities.ConclusionThis study enhances our understanding of wellbeing among rural veterans, emphasizing the importance of considering service-connected disabilities and health conditions. The findings underscore the need for targeted interventions and support systems tailored to the specific needs of rural veterans, particularly those with service-connected disabilities. Recognizing and addressing these factors are crucial steps toward enhancing the overall wellbeing of this population.